Drug Therapy for Non-Alcoholic Steatohepatitis-Induced Liver Fibrosis - D. V. Garbuzenko (Российский журнал гастроэнтерологии, гепатологии, колопроктологии, 2022)
Aim. An overview of current pharmacotherapy for non-alcoholic steatohepatitis (NASH)-associated liver fibrosis.Key points. In current clinical recommendations, therapeutic measures in non-alcoholic fatty liver disease should include lifestyle change, body weight normalisation, NASH-associated liver fibrosis-specific drug therapy and treatment for metabolic syndrome-related diseases. Given a lack of approved antifibrotic therapies in NASH, several drugs have nevertheless demonstrated an adequate efficacy and safety in phase 3 clinical trials, also in compensated cirrhosis, which allows their practical validation in phase 4.Conclusion. The understanding of liver fibrosis as an adverse natural consequence of non-alcoholic fatty liver disease clearly attests for an early introduction and wide use of antifibrotic therapy to improve NASH outcomes and avoid associated complications.